1996
DOI: 10.1590/s0074-02761996000200019
|View full text |Cite
|
Sign up to set email alerts
|

Tumor necrosis factor-α in human American tegumentary leishmaniasis

Abstract: Tumor necrosis factor-alpha (TNF-α) is a cytokine produced

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
52
0
3

Year Published

1997
1997
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 72 publications
(58 citation statements)
references
References 27 publications
1
52
0
3
Order By: Relevance
“…This can be related to the severity and exacerbated hypersensitivity of the mucosal disease leading to longer periods for resolution of lesions after therapy. In fact, a complete resolution of the mucosal lesions is usually observed about 6 months after therapy, whereas CL lesions are frequently healed even before the end of therapy (13,24). Moreover, we observed that ML patients during active disease had significantly higher production of type 1 (IFN-␥) and type 2 (IL-4 and IL-5) cytokines compared to patients with CL.…”
Section: Discussionmentioning
confidence: 69%
See 2 more Smart Citations
“…This can be related to the severity and exacerbated hypersensitivity of the mucosal disease leading to longer periods for resolution of lesions after therapy. In fact, a complete resolution of the mucosal lesions is usually observed about 6 months after therapy, whereas CL lesions are frequently healed even before the end of therapy (13,24). Moreover, we observed that ML patients during active disease had significantly higher production of type 1 (IFN-␥) and type 2 (IL-4 and IL-5) cytokines compared to patients with CL.…”
Section: Discussionmentioning
confidence: 69%
“…Moreover, we observed that ML patients during active disease had significantly higher production of type 1 (IFN-␥) and type 2 (IL-4 and IL-5) cytokines compared to patients with CL. Previous studies have associated the induction of cytokines such as IFN-␥ or tumor necrosis factor alpha, as well as the increased expression of mucosal IL-4 in mucosal lesions with the pathogenesis of the disease (5,6,13,26). Thus, it is likely that the observed exacerbated hypersensitivity to leishmanial antigens in ML associated with high production of both cytokine types may have a detrimental effect, contributing to the severity of the disease (5,6,13,27).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…High levels of TNF-α leave the beneficial action over the defense cells with autocrine and paracrine actions, to exert more general actions, of endocrine character, not favoring the inflammatory process (Vissers et al 1989, Jaattela 1991, Abbas et al 1995, Da-Cruz et al 1996. The observations with the Ptx-0 subgroup seem to result from a pronounced action of the defense cells stimulated by the levels of TNF-α modulated by pentoxifylline.…”
Section: Discussionmentioning
confidence: 99%
“…We do not know whether there is any association between susceptibility to leishmaniasis and the phenomenon of persistence, or whether all the findings in murine models infected with L. major, may eventually be valid for human infections with L. braziliensis (Da-Cruz et al 1996), but it seems logical that persistence must reflect a delicate interplay between the parasite and its host. Some Leishmania genotypes in a given population, taking into consideration their clonal structure (Tibayrenc et al 1990), may persist by their capacity to elicit a milder leishmanicidal action, avoiding the exacerbation of the host immune system and causing minor harmful effects to the host.…”
Section: Why Persistent Infections?mentioning
confidence: 99%